2015
DOI: 10.1007/s11356-015-4882-z
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium toxicity in Maize (Zea mays L.): consequences on antioxidative systems, reactive oxygen species and cadmium accumulation

Abstract: Increased cadmium (Cd) accumulation in soils has led to tremendous environmental problems, with pronounced effects on agricultural productivity. Present study investigated the effects of Cd stress imposed at various concentrations (0, 75, 150, 225, 300, 375 μM) on antioxidant activities, reactive oxygen species (ROS), Cd accumulation, and productivity of two maize (Zea mays L.) cultivars viz., Run Nong 35 and Wan Dan 13. Considerable variations in Cd accumulation and in behavior of antioxidants and ROS were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 253 publications
(120 citation statements)
references
References 48 publications
7
100
0
4
Order By: Relevance
“…Cadmium accumulation in cultivated soil has considerably increased over the last decade, and most crop plants, including maize, suffer from Cd toxicity in polluted environments (Valko et al, 2005; Anjum et al, 2015). Therefore, determining the molecular mechanisms involved in the responses to Cd stress would enable researchers to explore the potential Cd-defensive strategies that may occur in maize plants.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium accumulation in cultivated soil has considerably increased over the last decade, and most crop plants, including maize, suffer from Cd toxicity in polluted environments (Valko et al, 2005; Anjum et al, 2015). Therefore, determining the molecular mechanisms involved in the responses to Cd stress would enable researchers to explore the potential Cd-defensive strategies that may occur in maize plants.…”
Section: Discussionmentioning
confidence: 99%
“…Roots are the first organ exposed to Pb and thus can be a major storage organ for Pb (mostly in tolerant cultivars) or can play an intermediary role for exporting the Pb ions from soil to the aboveground plant parts (in case of sensitive cultivars) (Fangmin et al 2006). Unlike some other higher plants, i.e., maize (Anjum et al 2015) and Brassica (Ali et al 2014), rice is neither a better metal accumulator (plants that are able to biodegrade or biotransform the pollutants/contaminants from active to inactive form in their tissues and may survive even at high levels of contaminates in their tissues) nor a good metal excluders (that restrain the uptake of contaminants in to their organs and avoid to make a part of their biomass; however, can be regarded as a good indicator (translocate and accumulate metals to different organs depending on the environmental toxicity and genotype) (Liu et al 2003). However, different rice genotypes show differential uptake and translocation properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been repeatedly shown that the antioxidant enzyme activities are activated under heavy metal stresses (Schützendübel et al, 2001, 2002; Rozpądek et al, 2014; Chen et al, 2015; Tan et al, 2015). The enhanced activities of superoxide dismutase, peroxidase, catalase, and ascorbate peroxidase play an important role in scavenging the Cd 2+ -elicited H 2 O 2 in plants (Garg and Aggarwal, 2012; Anjum et al, 2015; Tan et al, 2015). To combat Cd 2+ -induced superoxide and H 2 O 2 , P. × canescens plants were found to rely mainly on antioxidant enzymes and the formation of the potential radical scavenging molecules, such as proline, sugar alcohols and soluble phenolics (He et al, 2011).…”
Section: Discussionmentioning
confidence: 99%